2022
DOI: 10.1016/j.psj.2021.101549
|View full text |Cite
|
Sign up to set email alerts
|

Glycyrrhiza polysaccharides can improve and prolong the response of chickens to the Newcastle disease vaccine

Abstract: Licorice is a medicinal and food plant widely used to treat diseases and produce food additives, because of its unique chemical constituents like polysaccharides, flavones, and saponins. Glycyrrhiza Polysaccharides ( GPS-1 ) are water-soluble neutral polysaccharides extracted from licorice. Currently, GPS-1 is administrated to chickens by gavage every d for 14 d to observe the impact of GPS-1 on the Newcastle disease vaccine. To determine the immunity of these chickens to NDV, blood seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 48 publications
3
14
0
Order By: Relevance
“…Researchers have also demonstrated a positive correlation between the immune activity of polysaccharides and their uronic acid content (9). Our previous study also confirmed that glycyrrhiza polysaccharides can prolong the efficacy and duration of the Newcastle disease virus (NDV) vaccine (10) and improve the intestinal immune function and microbial composition of roosters (4). In addition, the glycyrrhiza polysaccharide (GiP-B1) can cause significant phenotypic changes in dendritic cells (DCs) and the improvement of bioactive functions with a mechanism of action related to the TLRs/NF-B signaling pathway (11).…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…Researchers have also demonstrated a positive correlation between the immune activity of polysaccharides and their uronic acid content (9). Our previous study also confirmed that glycyrrhiza polysaccharides can prolong the efficacy and duration of the Newcastle disease virus (NDV) vaccine (10) and improve the intestinal immune function and microbial composition of roosters (4). In addition, the glycyrrhiza polysaccharide (GiP-B1) can cause significant phenotypic changes in dendritic cells (DCs) and the improvement of bioactive functions with a mechanism of action related to the TLRs/NF-B signaling pathway (11).…”
Section: Introductionsupporting
confidence: 75%
“…Using our previously reported methods ( 10 ), crude Glycyrrhiza polysaccharide (GPS) was extracted by boiling water from licorice ( Glycyrrhiza uralensis ) and then precipitated with 50% ethanol into GPS 50 extract ( 12 ). Proteins were removed five times, sequentially, using the Sevag method.…”
Section: Methodsmentioning
confidence: 99%
“… Liao et al (2021) reported that oral administration of APS could promote the production of secretory IgA in ileal mucosa of Muscovy ducklings infected with Muscovy duck reovirus. Wu et al (2022) verified GPS as an immune booster capable of enhancing the antibody potency of the Newcastle disease vaccine in chickens. Consistent with these findings, we observed in this study that dietary APS and GPS supplementation promoted the humoral immune response of broilers, leading to elevation in serum IgA, IgM, and IgG concentrations.…”
Section: Discussionmentioning
confidence: 84%
“…In broilers, it has been reported that the addition of GPS in diet could mitigate lipopolysaccharide-induced inflammatory response ( Zhang et al, 2021 ). Moreover, a recent study showed that oral administration of GPS could improve and prolong the response of chickens to the Newcastle disease vaccine ( Wu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it has the potential to be used as adjuvant material for a vaccine. To identify the capability of ural LPs as immune boosters against Newcastle disease virus (NDV), Wu has showed that administration of LPs in a vaccinated chicken group could boost their immune response compared to the only vaccinated group [ 115 ]. Although this study did only oral administration of LPs which increased the response against the virus, it also gives a clue that LPs can be used as vaccine adjuvant in future formulations.…”
Section: Uses Of Lps As Biopolymermentioning
confidence: 99%